TOPICAL ISSUES OF EDUCATIONAL LAW IN THE CONDITIONS OF DIGITAL TRANSFORMATION OF THE EDUCATION - Elena S. Balashova; Lyudmila V. Gnetova; Ekaterina S. Surovegina (Russian Studies in Law and Politics)
Background. The article is devoted to the study of factors standing in the way of improving educational law as a branch. The relevance of the study is due to the innovative processes developing at the present stage both in the field of educational law and in the field of education. The education system in Russia in the transition from the Bologna process to a new paradigm of education needs to improve educational law. In the course of the study, the most problematic aspects of the regulatory framework for education were analyzed.